2021
DOI: 10.1101/2021.05.16.444366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rho Kinase regulates neutrophil NET formation that is involved in UVB-induced skin inflammation

Abstract: Objective. Ultraviolet B (UVB) is an important trigger of skin inflammation and lupus with recruitment of leukocytes to inflamed skin. Neutrophil NETosis has been implicated in pathogenesis of lupus erythematosus. We recently reported that nuclear envelope rupture and NET formation is driven by PKCα-mediated nuclear lamin B disassembly, with involvement of NETosis in UVB-induced skin inflammation. Studies have shown that cytoskeletal networks are involved in NETosis. However, it is still unknown how cytoskelet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 96 publications
(293 reference statements)
0
10
0
Order By: Relevance
“…On the other hand, based on data from endothelial cells, it has been proposed that Rap1 binding to KRIT1 facilitates the inactivation of RhoA/ROCK [31,51,52]. As RhoA/ROCK activity is also important for neutrophil function [53][54][55][56][57], that KRIT1 could also regulate RhoA in neutrophils is an attractive hypothesis. Our data suggest that KRIT1 deficient neutrophils exhibit increased baseline RhoA/ ROCK activity, as shown by increased pMLC staining in vehicle-treated cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, based on data from endothelial cells, it has been proposed that Rap1 binding to KRIT1 facilitates the inactivation of RhoA/ROCK [31,51,52]. As RhoA/ROCK activity is also important for neutrophil function [53][54][55][56][57], that KRIT1 could also regulate RhoA in neutrophils is an attractive hypothesis. Our data suggest that KRIT1 deficient neutrophils exhibit increased baseline RhoA/ ROCK activity, as shown by increased pMLC staining in vehicle-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in endothelial cells have shown that KRIT1 is a negative regulator of RhoA and its effector Rho kinase (ROCK); loss of KRIT1 expression leads to increased RhoA/ROCK activity, phosphorylation of myosin light chain (MLC) and increased actin-myosin contractility [51,52]. In neutrophils, RhoA/ROCK has been shown to regulate adhesion and migration on multiple substrates [53][54][55][56][57]. Therefore, we examined the effect of KRIT1 depletion on RhoA/ROCK activity in neutrophils by measuring phospo-MLC levels using immunofluorescent microscopy.…”
Section: Loss Of Krit1 Reduces Neutrophil Spreading On Fibronectinmentioning
confidence: 99%
“…However, NET formation is a caspase-independent process [43,47,48], during which caspase-3 remains inactive [43]. Recent studies indicate that protein kinase C-α (PKC-α)-mediated lamin B phosphorylation and disassembly is responsible for nuclear envelope rupture [43,49]. In addition, cyclin dependent kinase 4/6 (CDK4/6) controls NET formation through modulation of lamin A/C phosphorylation, resulting in nuclear envelope rupture [38,50].…”
Section: The Process Of Net Formation and Degradationmentioning
confidence: 99%
“…Thus, kinase-mediated nuclear lamina phosphorylation-disassembly [43,50], but not proteolytic cleavage [38], is responsible for nuclear envelope rupture during NET formation. PKCα and CDK4/6 are located in the cytoplasm of resting neutrophils, and their nuclear translocation requires a functional actin cytoskeleton in the early stage of neutrophil activation [38,49,52]. Genetic [49,53] or pharmacologic [54] inhibition of actin assembly or its upstream regulatory molecules, Rho kinase [49] or Wiskott-Aldrich syndrome protein [53], impair NET formation.…”
Section: The Process Of Net Formation and Degradationmentioning
confidence: 99%
See 1 more Smart Citation